2015
DOI: 10.1021/jp512495v
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectroscopy of Warm and Neutral Phenol–Water Clusters

Abstract: Although many studies have been reported on structures of neutral water clusters, most of experimental information has been restricted to their most stable structures. With elevation of temperature, however, transient structures as well as higher energy stable structures can be formed, as recently demonstrated in small-sized neat water clusters (Zischang, J.; Suhm, M. A. J. Chem. Phys. 2014, 140, 064312). In the present study, we performed infrared spectroscopy of warm phenol-(H2O)2, which is an analogue of (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…With elevation of temperature of the cluster, however, higher energy isomers can be populated because of entropy. Therefore, to fully understand the hydrogen bond structure of the cluster, not only the most stable structure but also the temperature dependence of preferred structures is very important. …”
Section: Introductionmentioning
confidence: 99%
“…With elevation of temperature of the cluster, however, higher energy isomers can be populated because of entropy. Therefore, to fully understand the hydrogen bond structure of the cluster, not only the most stable structure but also the temperature dependence of preferred structures is very important. …”
Section: Introductionmentioning
confidence: 99%
“…Small clusters composed of a solute and selected numbers of protic solvent molecules bound via hydrogen bonded (H-bonded) networks serve as convenient models to study the solvation dynamics induced by light excitation. In this direction many studies have been reported in the past two decades where phenol–water clusters were used as the prototypical systems. An underlying dynamical process for all light-induced chemical events in molecules is occurrence of redistribution of excitation energy from the initially excited level to optically dark isoenergetic background levels, some of which correspond to reaction modes. For reactions occurring in the liquids most of the background energy levels could be produced due to solute–solvent interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the vibrational temperature of the cluster is approximately 100 K [13] that is far from 342 K used in the present study. At low temperature, the interaction of water with phenol is highly favored and would explain why it is detected at ~100 K and not at 342 K. This is supported by a conclusion from Shimamori et al [13] who showed that a small increase of temperature from 140 to 175 K induces a strong modification of the H-bonded structure of a (1:2) phenol:water cluster leading to a strong decrease of the ν(OH) band shift. It is thus proposed that in our present study, the more than 200 K higher temperature would not induce any variation of the position and of the ε values of the considered bands.…”
Section: Analysis Under Static Conditionsmentioning
confidence: 80%
“…This appears consistent with results from Watanabe et al [10] who experimentally showed an increase of the intensity of the ν(OH) groups by a factor 5 and 11 for a (1:1) and a (1:3) phenol:water cluster respectively. However, as highlighted by Shimamori et al [13], the phenol-water clusters in the above cite studies were generated using a supersonic jet expansion. Consequently, the vibrational temperature of the cluster is approximately 100 K that is far from that encountered in typical conditions used for chemical analysis of interest in the present paper.…”
mentioning
confidence: 99%